2013
DOI: 10.1166/jbn.2013.1489
|View full text |Cite
|
Sign up to set email alerts
|

Micelles of Methoxy Poly(ethylene glycol)–Poly(ε-caprolactone) as a Novel Drug Delivery Vehicle for Tacrolimus

Abstract: As a traditional immunosuppressive drug, tacrolimus showed the potency in treating ulcerative colitis. In this study, a novel drug delivery vehicle achieved by self-assembly was applied to tacrolimus. During the preparation, amphiphilic copolymer MPEG-PCL was chosen to form the unique core-shell structure, and tacrolimus was loaded into the hydrophobic core due to its great hydrophobicity. After several relevant tests, MPEG-PCL (2000-2000) was selected to be the most suitable and safest copolymer for drug carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Therefore, in this study, we propose a combination of PCL and the soluble polyethylene glycol (PEG), a polymer reputed for its biocompatibility, tissue reaction, and biodegradation kinetics [19], and, respectively, for its hydrophilicity, nontoxicity, nonimmunogenicity and absence of antigenicity [9,20,21]. The PEG-based materials designed for biomedical applications include scaffolds [22], micelles [23], nanoparticles [24], and coatings [25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, we propose a combination of PCL and the soluble polyethylene glycol (PEG), a polymer reputed for its biocompatibility, tissue reaction, and biodegradation kinetics [19], and, respectively, for its hydrophilicity, nontoxicity, nonimmunogenicity and absence of antigenicity [9,20,21]. The PEG-based materials designed for biomedical applications include scaffolds [22], micelles [23], nanoparticles [24], and coatings [25].…”
Section: Introductionmentioning
confidence: 99%
“…Ola presents with a series of physicochemical properties, such as poor solubility, low bioavailability, and an extensive range of tissue toxicity that largely offset the use and therapeutic benefits of Ola. In our previous study, we demonstrated that MPEG-PCL nanoparticles were outstanding carriers for hydrophobic drugs in virtue of the hydrophilic Time (days) Body weight (g) 28 34 PEG segment being introduced into PCL backbones. [25][26][27][28] Therefore, in our study, MPEG-PCL was used as a carrier to prepare Ola-NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were sacrificed 24 h after the last drug loaded hydrogels administration. Their distal colons were resected and collected (Wang et al, 2012). Specimens were taken from the collected colon, and then, the specimens were fixed in neutral formalin and embedded in paraffin.…”
Section: Animal Treatmentmentioning
confidence: 99%